Cross-Correlated Relaxation of Dipolar Coupling and Chemical-Shift Anisotropy in Magic-Angle Spinning R(1ρ) NMR Measurements: Application to Protein Backbone Dynamics Measurements - Kurauskas, Vilius (J Phys Chem B, 2016)
Transverse relaxation rate measurements in MAS solid-state NMR provide information about molecular motions occurring on nanoseconds-to-milliseconds (ns-ms) time scales. The measurement of heteronuclear ((13)C, (15)N) relaxation rate constants in the presence of a spin-lock radio-frequency field (R(1ρ) relaxation) provides access to such motions, and an increasing number of studies involving R(1ρ) relaxation in proteins has been reported. However, two factors that influence the observed relaxation rate constants have so far been neglected, namely (i) the role of CSA/dipolar cross-correlated relaxation (CCR), and (ii) the impact of fast proton spin flips (i.e. proton spin diffusion and relaxation). We show that CSA/D CCR in R(1ρ) experiments is measurable, and that this cross-correlated relaxation rate constant depends on ns-ms motions, and can thus itself provide insight into dynamics. We find that proton spin-diffusion attenuates this cross-correlated relaxation, due to its decoupling effect on the doublet components. For measurements of dynamics, the use of R(1ρ) rate constants has practical advantages over the use of CCR rates, and the present manuscript reveals factors that have so far been disregarded and which are important for accurate measurements and interpretation.